Development of ABEL KERINDO Interactive Multimedia based on Articulate Storyline to Learn Social Science for Alpha Generation Students in Elementary School - Divandari Setya Putri; Farid Ahmadi (Universitas Negeri Malang, 2024)
Minimizing the use of technology-based interactive multimedia in social science learning reduces the interest and learning outcomes of alpha-generation students. Research and development (R&D) design with a waterfall development model, which includes requirements, design, Implementation, verification, and maintenance phases, is used in this research. Developing interactive multimedia product ABEL KERINDO